2019
DOI: 10.1111/jcmm.14625
|View full text |Cite|
|
Sign up to set email alerts
|

LINC01133 inhibits breast cancer invasion and metastasis by negatively regulating SOX4 expression through EZH2

Abstract: Mounting evidence highlights long non‐coding RNAs (lncRNAs) as crucial regulators in multiple types of biological processes and contributing to tumourigenesis. LINC01133, located in chromosome 1q23.2, was a recently identified novel lncRNA with a length of 1154nt. It was involved in the development of colorectal cancer and non‐small cell lung cancer. However, its clinical relevance, biological functions and potential molecular mechanism in breast cancer are still unclear. In this study, we found that the LINC0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(47 citation statements)
references
References 32 publications
1
45
0
Order By: Relevance
“…LINC00511 51 and LINC01133. 52 Of note, LINC00460 has been unravelled to play a positive role in EMT progress in HNSCC, 53 and LINC00460 was in a significantly higher expression level in OSCC tissues compared with the normal tissues validated by the GEPIA database ( Figure 6). As shown in Figure 4B, LINC00460 was predicted to be in a co-expression pattern with VEGFA, which has been proved to be overexpressed in aggressive OSCC.…”
Section: Discussionmentioning
confidence: 99%
“…LINC00511 51 and LINC01133. 52 Of note, LINC00460 has been unravelled to play a positive role in EMT progress in HNSCC, 53 and LINC00460 was in a significantly higher expression level in OSCC tissues compared with the normal tissues validated by the GEPIA database ( Figure 6). As shown in Figure 4B, LINC00460 was predicted to be in a co-expression pattern with VEGFA, which has been proved to be overexpressed in aggressive OSCC.…”
Section: Discussionmentioning
confidence: 99%
“…This fact suggests that ANCR may participate in the TGF-β1-induced metastasis through other mechanisms than EZH2 degradation. Along with more intensive studies, an increasing number of tumor suppressor lncRNAs have been discovered, e.g., PDCD4-AS1 22 , LINC01133 57 , NORAD 58 , MEG3 59 , XIST 60 63 , etc. Growing evidence indicates that lncRNAs may become a promising biomarker in breast cancer metastasis.…”
Section: The Dual Function Of Lncrnas In Breast Cancer Metastasismentioning
confidence: 99%
“… LncRNA Functions Functional mechanism Refs. MALAT1 ↓ Migration, invasion, metastasis Scaffold molecules, transcriptional regulation, PI3K/AKT pathway 52 , 95 NKILA ↓ Migration, invasion, metastasis Protein stability, transcriptional regulation, scaffold molecules, NF-κB pathway 54 ANCR ↓ Migration, invasion, metastasis Protein stability, transcriptional regulation, TGFβ pathway 29 PDCD4-AS1 ↓ Migration mRNA stability 22 LINC01133 ↓ Migration, invasion, metastasis Transcriptional regulation 57 XIST ↓ Migration, invasion, metastasis ceRNA 61 CASC2 ↓ Migration, invasion, metastasis ceRNA 166 MEG3 ↓ Migration, invasion PI3K/AKT pathway 127 NORAD ↓ Migration, invasion, metastasis YAP pathway Decoy 58 GAS5 ↓ Invasion ceRNA 96 LIMT ↓ Migration, invasion, metastasis EGF pathway 93 …”
Section: The Dual Function Of Lncrnas In Breast Cancer Metastasismentioning
confidence: 99%
“… 4 , 5 Emerging studies have suggested that lncRNAs play important roles in the initiation and progression of human cancers. 6 , 7 Numerous studies show that lncRNA is involved in CRC development. 8 , 9 LINC01224 was a novel identified lncRNA.…”
Section: Introductionmentioning
confidence: 99%